Karakteristik Akseptor Kb Baru Dan Aktif Dalam Pemilihan Metode Kontrasepsi Suntik Di Wilayah Gajahan Surakarta - Fiqih Faruz Romadhon; Endang Sutisna; AA Subijanto (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background : Based the data of Central Java Provincial Health Office 2006, see that the most choice of contraceptive method is injectable . Health behaviors included the selection of contraceptive is influenced by three factors: predisposing, enabling, and driving. Researcher aims to determine the relationship of the characteristics of new family planning acceptors and active in particular the level of knowledge, level of education and employment with the selection of injectable contraceptive method. Methods : Samples: new and active acceptors of family planning in Gajahan Health Centre, Surakarta. The number of sample: 86 persons. Sampling technique: simple random sampling. The research instrument: questionnaire. Then the data was analyzed using chi square test. Results: The statisctical test of level of knowledge showed that (X2) of 6.880 with a significance (p) of 0.009. Then, the statistical result test of level of formal education showed that (X2) of 2.140 with significance (p) of 0.144. The statistical test of the employment status showed that (X2) of 6.351 with a significance (p) of 0.012. Results of statistical tests of regression analysis can be seen that the level of knowledge is the most dominant factor with value of statistical test (wald) is 4.084 and the greatest significance (p) is the smallest 0.043. Conclusions : 1) There is a correlation between the level of knowledge with the election of injection method 2) There was no relationship between the level of education with the election of injection method 3) There is a relationship between employment status with the election of injection method 4) The level of knowledge is the most dominant factor associated with the selection of injectable contraceptives. Keywords: family planning, injection, knowledge, formal education, employment status